Sustainable Development Strategy and Integration of the “Borovella” Plantation into the Tourism Offer of the Municipality of Topusko - Mizić, Almaida; Stanojević, Andrej (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
The paper presents a proposed strategy for the sustainable development of the Borovella plantation in the municipality of Topusko, focusing on the expansion of its capacity and its inclusion in the tourist offer. The aim is to transform the plantation into a recognisable centre for organic production, rural tourism and education. The company's vision is based on four main priorities. The first priority focuses on expanding the plantation and introducing new varieties adapted to the local climate, which would increase production capacity and enable export. The second priority includes the development of tourism activities through the promotion of accommodation facilities, such as holiday homes, which would make the plantation an attractive destination for nature lovers. The third priority relates to educational workshops for tourists, schools and families, where visitors would have the opportunity to learn about ecology and sustainable practices in agriculture. The fourth priority involves working with local producers to create a gastronomic product - breakfast in a basket - with the aim of promoting local delicacies and strengthening the economy. The proposed priorities focus on Borovella's long-term vision as a sustainable and innovative business that combines agricultural production with tourism offerings, promoting sustainable development and community connectivity.